A Review of Amitav Ghosh Novels - Sharma, Dr. Dinesh (Innovative Research Thoughts, 2017)
Many of the most recent Indian English novels created by emigrant authors draw inspiration from current Indian socio-cultural events. They also study the link between the East and the West. It's a common topic in modern Indian English literature because of the medium used by the author. The Indian English novel's reinterpretation of mythology and history has gained new meaning and potential. He often returns to the mythology and history of India in his writing. “There are three films that deal with the Muslim mentality as it is entangled with Indian history and culture: Midnight's Children, Shame, and The Moor's Last Sigh. To express the Indians' blind allegiance to the English, the clash of western rationality with Indian myth, and the emptiness of national identity and national boundaries, The Circle of Reason, The Calcutta Chromosome, and The Shadow Lines (1988) were published. Amitav Ghosh, who has received several honours, including the Sahitya Akademi Award and the Prix Medicis Etrangere of France for his works. His writing on colonialism and its impact on indigenous peoples has been described as some of the most poetic and profound in the history of literature. The Circle of Reason, The Glass Palace, The Calcutta Chromosome, and The Hungry Tide are among his works.